Azadirachta indica Leaf Extract Ameliorates Hyperglycemia and Hepatic Glycogenosis in Streptozotocin-induced Diabetic Wistar Rats - Oluwole B. Akinola,; Olufunke O. Dosumu,; Oluwafunmike S. Akinola,; Laura Zatta,; Luciana Dini,; Ezekiel A. Caxton-Martins, (International Journal of Phytomedicine, 2010)
We studied the effects of ethanolic leaf extract of Azadirachta indica (AIE) on hepatic microscopic anatomy and oxidative stress markers in diabetic rats. Seventy-five Wistar rats (8 weeks old) were randomly assigned to five treatment groups: control; diabetic; diabetic+AIE; AIE only; and diabetic+glibenclamide. Hyperglycemia was induced in fasted rats with streptozotocin. AIE was administered orally at 500 mg/kg bw/d and glibenclamide at 600 μg/kg bw/d for 50 days (50 d). Animals were sacrificed on treatment days 7, 21 and 50. The liver was stained with PAS. Hepatic markers of oxidative stress were also estimated. At 50 d, histological study of the liver of diabetic rats showed swollen PAS+ hepatocytes, whose content was confirmed to be glycogen. On the contrary, hepatocytes of AIE-treated diabetic rats lacked glycogen. The major finding in these rats was exacerbated oxidative stress. Our findings in this model showed the beneficial effect of AIE in the amelioration of diabetic hepatic glycogenosis.